The Role of Radiotherapy towards Pediatric Cancer - Agustinus Darmadi Hariyanto; Hari Murti Wijaya; Jellyca Anton; Seize Edwiena Yanuarta; Steven Octavianus; Handoko Handoko; Endang Nuryadi; Soehartati Argadikoesoema Gondhowiardjo (Radioterapi & Onkologi Indonesia, 2020)
Cancer is the leading cause of death in children worldwide. Pediatric cancer is challenging to detect early because it generally appears with signs and symptoms that are not typical. The increase in cancer cases in pediatric must be followed by an increase in cancer management in all fields of scientific disciplines. Radiation oncology, as one of the areas of science, has an essential role in definitive, adjuvant, palliative, and prophylactic cancer in pediatric. Apart from these uses, radiation management is a significant contributor to the complications of pediatric cancer survivors. Complications that arise can be in the form of growth retardation, tissue changes, secondary cancer, neurocognitive changes, infertility, or other hormonal dysfunction and preterm labor. An increase in radiation techniques followed the development of treatment machines able to reduce radiation-related morbidity and mortality rates. In pediatric radiotherapy, the entire process from the pre-procedure anesthesia to radiotherapy requires special attention. Psychological issues are also worth observing. This study will briefly discuss these matters and the management of some of the most common pediatric cancers in Dr. Cipto Mangunkusumo Hospital.